VIGS in afrika, met spesiale verwysing na Suid-Afrika - Viljoen, A. T. (Koers, 1990)
It is generally accepted that Africa is the continent that is most seriously affected by the AIDS epidemic. As a result of under-reporting, the actual incidence of AIDS may be more than ten times higher than indicated by the official figures. The majority of females of child-bearing age can be infected within the next 4-6 years. Infant mortality is expected to increase dramatically. Up to 50% of babies born to HIV-infected mothers are also infected. Most of these babies will develop an AIDS-related illness and die at a very young age. Twelve factors have been identified which place the black population of South-Africa among the highest risk groups in the world. No vaccine or cure is available at this stage. Education of the general population, with the aim to bring about a change in sexual practices, is the only way to prevent a demographic catastrophe in this country.